PENYELESAIAN PEMBIAYAAN BERMASALAH PADA LEMBAGA KEUANGAN SYARIAH STUDI BMT AL HASANAH LAMPUNG TIMUR - Aye Sudarto (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2020)
All financial institutions in providing financing do not want the financing to experience problems, but nevertheless problems often arise. BMT Al Hasanah in handling problem financing needs to carry out financing handling strategies by taking several actions so as not to cause losses. How to handle problematic financing of problem financing products by conducting intensive billing, giving warnings in the form of warning letters, conducting resheduling and restructuring.